Predicting onion production through Neuro-Fuzzy to fulfill national demand - Tri Sandhika Jaya; Henry Kurniawan (Jurnal Ilmiah ESAI, 2014)
Onion prices experienced a sharp rise in prices, because there was not enough stock to meet the demand. Hence more onion production to meet those needs is required. Onion production is influenced by the harvested area and productivity. Determining the amount of onion production can be done through prediction. Predictions made by the neuro-fuzzy method in this study combine two concepts, namely the concept of fuzzy logic and neural networks. The results of the research are obtained by comparing the real data with the predicted results to determine the accuracy of this method.Keywords: production, neuro-fuzzy, fuzzy logic, neural network, predicted